PENDIDIKAN SISTEM GANDA (PSG) PADA SMK MUHAMMADIYAH 3 KARANGANYAR SPESIALIS OTOMOTIF - Fathoni, Ahmad; Pramono, Pramono (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2014)
This research is a qualitative study has three purposes.1 ) To describe thecharacteristics of learners PSG. 2) To describe the characteristics of PSGteachers. 3 ) To describe the learning characteristics of PSG. This research wasconducted at SMK Muhammadiyah 3 Karanganyar with in-depth interviews, directobservation and the use of documents for data collection. The data source of this research istaken from the principal, vice principal, chairman of the skills program, working group PSG,PSG executive teacher, head of partner institutions, and recording learning activities atschool and in industry. The Result of this shows that : 1) The learners had an average value5.29 of National Exam, not color blind and having minimum height 142 cm,57, 9%responsiveand99.7%had agoodpersonality. Economic background of their parents is middleand lower class. Learners have different characteristics which must be understood by theteacher. 2) Teacher background S1, has teaching experience at least 1 year, activelyimprove their competence through training and industry internship andhave agoodperformance. 3) Learning PSG using pattern learning by placing the school as a replica ofthe industry.